How relationship-oriented behavior influences employee voice-silence conversion in cross-cultural virtual teams: the mediating role of psychological safety - Dong, Xuetong; Xing, Luling (Frontiers in Psychology, 2026)
IntroductionThis study examines how leader relationship-oriented behavior influences employee voice-silence conversion in cross-cultural virtual teams through digital contexts.MethodsUsing structural equation modeling with data from 342 team members across 68 virtual teams spanning 23 countries, we test a moderated mediation model that positions psychological safety as a key mediating mechanism.ResultsResults demonstrate that relationship-oriented behavior significantly promotes voice-silence conversion toward increased voice behaviors (β = 0.34, p < 0.001), with psychological safety serving as a critical mediator (indirect effect β = 0.24, p < 0.001). Cultural value differences negatively moderate this relationship (β = −0.18, p < 0.05), while digital tool usage frequency enhances the effectiveness of relationship-oriented behaviors (β = 0.15, p < 0.05).DiscussionThe findings extend leadership theory by demonstrating how traditional relationship-oriented approaches can effectively operate in digitally-mediated cross-cultural contexts, while advancing understanding of voice-silence as dynamic conversion processes rather than static behavioral states. Practical implications suggest that organizations should prioritize relationship-building competencies among virtual team leaders while recognizing that cultural diversity requires adaptive leadership approaches and that digital technologies can amplify rather than constrain interpersonal leadership effectiveness.